What Is All the Hype About Height? A Semiotic Analysis of Sports Media, Smaller Athletes, and Ideology - Cameron, Paul (Université d'Ottawa / University of Ottawa, 2012)
This study looks at how professional male athletes—particularly undersized athletes—are represented throughout televised sport. Based on the assumption that televised sport is a gendered and predominantly masculine genre, the focus of this analysis is to demonstrate whether or not professional male athletes are evaluated differently based on physical stature, and whether or not such representations reinforce a dominant—mythic—male ideology. Grounded mainly in Gramscian hegemony and Peircean semiotics, the subsequent analysis compares broadcast commentary and visuals taken from the 2010 men’s Olympic ice hockey tournament and the 2010 men’s FIFA World Cup. In both events, it was generally found that taller athletes were praised more positively than smaller athletes. These findings appear to support common sports-related stereotypes, such as, the apparent media-reinforced expectation that professional male athletes be almost inhuman, mythical representations of ordinary men, i.e., the best athletes should be large, intimidating, aggressive, and hyper-masculine symbols.
Keywords: Human Height; Masculinity; Ideology; Myth; Semiotics; Sports Media